Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1128/aac.01086-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Interactions of Antimicrobial Combinations with Fosfomycin against KPC-2-Producing Klebsiella pneumoniae and Protection of Resistance Development

Abstract: Using time-kill methodology, we investigated the interactions of fosfomycin with meropenem or colistin or gentamicin against 17 genetically distinct Klebsiella pneumoniae clinical isolates carrying bla KPC-2 . Synergy was observed with meropenem or colistin against 64.7 and 11.8% of tested isolates, while the combination with gentamicin resulted in indifference. All studied combinations showed improved bactericidal activity, compared to fosfomycin alone and prevented the development of fosfomycin resistance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 14 publications
(9 reference statements)
2
60
1
6
Order By: Relevance
“…A similar approach for reading disk diffusion has been proposed by others (18,29). It can be argued that also from a clinical point of view, it might be appropriate to ignore a certain subpopulation of fosfomycinresistant mutants when reading susceptibility tests, because intravenous fosfomycin is mostly used in combination therapy for infections caused by multidrug-resistant Enterobacteriaceae (5), and combination therapy has been shown to prevent the development of fosfomycin resistance (30). It is an open question as to which fosfomycin susceptibility testing method best predicts treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach for reading disk diffusion has been proposed by others (18,29). It can be argued that also from a clinical point of view, it might be appropriate to ignore a certain subpopulation of fosfomycinresistant mutants when reading susceptibility tests, because intravenous fosfomycin is mostly used in combination therapy for infections caused by multidrug-resistant Enterobacteriaceae (5), and combination therapy has been shown to prevent the development of fosfomycin resistance (30). It is an open question as to which fosfomycin susceptibility testing method best predicts treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, combinations of antibiotics are commonly administered to patients with severe infections either empirically to broaden the coverage or definitively for polymicrobial infections (37,38). Evidence derived from clinical and in vitro studies reveals that a combination of antibiotics might prevent the emergence of resistant strains during therapy (39,40). However, clinical data do not clearly support the idea that antibiotic combinations reduce the emergence of resistance (41).…”
Section: Discussionmentioning
confidence: 99%
“…77 Some in-vitro data suggest synergy in combining two agents against carbapenemase-producing K. pneumoniae, even when the pathogen is resistant to one of these agents. 78,79 Synergy was claimed for a combination of polymyxin B and either rifampin or doxycycline, resulting in at least a four-fold decrease in the MIC of polymyxin B when both drugs were used at physiologically achievable concentrations in one study. 78 In another study a combination of fosfomycin with meropenem or colistin was asserted to be synergistic, based on 100-fold more extensive killing than with the more active single agent.…”
Section: Combination Therapy In Infections Due To Resistant Gram-negamentioning
confidence: 99%
“…78 In another study a combination of fosfomycin with meropenem or colistin was asserted to be synergistic, based on 100-fold more extensive killing than with the more active single agent. 79 Nevertheless there is a profound lack of clarity on when and how the various different measures of synergy used in vitro translate into clinical advantage; moreover there must be a concern about publication bias: studies that detect synergy are more likely to be reported and published than those that fail to do so.…”
Section: Combination Therapy In Infections Due To Resistant Gram-negamentioning
confidence: 99%